The genetics of glutamate oxaloacetate transaminase (GOT) in Pinus merkusii Jungh. et de Vriese - ISKANDAR ZULKARNAEN SIREGAR; TEDI YUNANTO (Biodiversitas Journal of Biological Diversity, 2010)
Siregar IZ, Yunanto T. (2010). The genetics of glutamate oxaloacetate transaminase (GOT) in Pinus merkusii Jungh. et de Vriese. Biodiversitas 11: 5-8. Inheritance and linkage analysis of glutamate oxalacetate transaminase (GOT) in P. merkusii were performed using megagametophyte tissues of single tree seed-lots. One monomorphic locus (GOT-A) and three polymorphic loci (GOT-B,GOT-C and GOT-D) were identified, based on the allelic 1: 1 segregation of putatively heterozygous trees. Linkage analysis revealed that GOTC and GOT-D were closely linked loci with an average recombination rate (R) of about 5%. This result which is in contrast to the GOT genetics in other pine species was discussed with regard to the probably occurring gene duplication of one GOT locus.